Differential expression of αVβ3 and αVβ6 integrins in prostate cancer progression - Quaglia, Fabio (PLoS One, 2021)
Neuroendocrine prostate cancer (NEPrCa) arises de novo or after accumulation of genomic alterations in pre-existing adenocarcinoma tumors in response to androgen deprivation therapies. We have provided evidence that small extracellular vesicles released by PrCa cells and containing the αVβ3 integrin promote neuroendocrine differentiation of PrCa in vivo and in vitro. Here, we examined αVβ3 integrin expression in three murine models carrying a deletion of PTEN (SKO), PTEN and RB1 (DKO), or PTEN, RB1 and TRP53 (TKO) genes in the prostatic epithelium; of these three models, the DKO and TKO tumors develop NEPrCa with a gene signature comparable to those of human NEPrCa. Immunostaining analysis of SKO, DKO and TKO tumors shows that αVβ3 integrin expression is increased in DKO and TKO primary tumors and metastatic lesions, but absent in SKO primary tumors. On the other hand, SKO tumors show higher levels of a different αV integrin, αVβ6, as compared to DKO and TKO tumors. These results are confirmed by RNA-sequencing analysis. Moreover, TRAMP mice, which carry NEPrCa and adenocarcinoma of the prostate, also have increased levels of αVβ3 in their NEPrCa primary tumors. In contrast, the αVβ6 integrin is only detectable in the adenocarcinoma areas. Finally, analysis of 42 LuCaP patient-derived xenografts and primary adenocarcinoma samples shows a positive correlation between αVβ3, but not αVβ6, and the neuronal marker synaptophysin; it also demonstrates that αVβ3 is absent in prostatic adenocarcinomas. In summary, we demonstrate that αVβ3 integrin is upregulated in NEPrCa primary and metastatic lesions; in contrast, the αVβ6 integrin is confined to adenocarcinoma of the prostate. Our findings suggest that the αVβ3 integrin, but not αVβ6, may promote a shift in lineage plasticity towards a NE phenotype and might serve as an informative biomarker for the early detection of NE differentiation in prostate cancer.